Choice blindness as a new tool to study preference change - Tärning,Betty (2007)
Recent research has shown that we might not be as aware of our choices as we believe ourselves to be - a phenomenon called choice blindness (Johansson et al, 2005). In this thesis I replicate and extend these results by showing that choice blindness can be used to unconsciously influence preferences. An experiment with four conditions was conducted. In all conditions, participants were shown two series of pictures of female faces, and were instructed to point to the one they found the most attractive. On some pairs they were also instructed to verbalize the reason behind their choice. Unknown to the participants on certain trial a card trick was used to covertly exchange one face for the other. In the second condition an extended verbal report was required. In the third condition a verbal report and an attractiveness rating was required. Finally, the fourth condition was a combination of condition two and three. The results showed (i) that in the card trick trials the participants often failed to notice the mismatch between their intended choice and the manipulated outcome, and (ii) that the outcome of the mismatched trials exerted a strong influence on the second choices made by the participants, and (iii) that this effect was moderated by the type and amount of feedback provided in the manipulated trials.
Keywords: choice blindness; preference; decision making; Social psychology; Socialpsykologi; Applied and experimental psychology; Tillämpad och experimentell psykologi